A Governança e o orçamento impositivo na Universidade Federal do Pará - LOPES, Lorena Suély Pires Silva (Universidade Federal do Pará, 2022)
The Impositional Budget makes the budgetary and financial execution of a certain percentage of parliamentary amendments on the public budget mandatory, characterizing itself as an important instrument for deputies and senators to effectively meet the demands of the communities they represent. This work had as a general objective to analyze the challenges of budget governance at the Federal University of Pará, taking into account the programmatic, participatory and accountability dimensions (OECD, 2014). To achieve this objective, the study was based on budget governance and the normative understanding that regulates the matter, through which it was possible to identify the dimensions and factors appropriate for this management. The data collection procedures used were participant observation, document verification, interviews with four managers of the institution and application of questionnaires. From the latter, 34 answered questionnaires were obtained, containing 20 items related to budget management practices. To analyze the qualitative data, content analyzes were performed, and for the questionnaires, descriptive statistical analysis. Thus, this research found challenges in the need for improvement in the three dimensions of governance, highlighting the need to strengthen the link between planning and execution (programmatic dimension), improving the participation of the results achieved (participatory dimension), and high risk of technical impediment and/or non-execution of resources through agreements (accountability dimension). From the analyzes carried out, this study generated as a product the main premises for improving the execution of parliamentary amendments and a draft resolution for the management of decentralized resources through agreements.